Discussion of Financial Distress in Private Colleges - Massy, William F. (Journal of Accounting Research, 1977)
William F. Massy, Discussion of Financial Distress in Private Colleges, Journal of Accounting Research, Vol. 15, Studies on Measurement and Evaluation of the Economic Efficiency of Public and Private Nonprofit Institutions (1977), pp. 46-51